The Festuco-Brometea grasslands on sandstone and marl-clay-sandstone substrata in Tuscany (northern-central Ita ly) - Foggi, Bruno; Lastrucci, Lorenzo; Gennai, Matilde; Viciani, Daniele (Hacquetia, 2015)
The grasslands dominated by Bromus erectus and/or Brachypodium rupestre cover large areas on sandstone and marl-clay-sandstone substrata (limestone is excluded), of the Apennines and pre-Apennines between Pistoia and Arezzo provinces (Tuscany, Central Italy). Our investigation was focused on to 71 unpublished relevés and 45 literature relevés from Tuscany and surrounding areas, reporting the original relevés of Astragalo monspessulani-Brometum erecti, Centaureo bracteatae-Brometum erecti and Ononido masquillerii-Brometum erecti. The relevés were submitted to exploratory multivariate analysis, allowing to detect nine distinct groups. Their consistence was verified by mean of NMDS against Ellenberg/Pignatti indicator values, and CCA constrained against chorotypes and growth forms. Diagnostic species of the definitive groups resulting from the analysis were chosen according to species fidelity, based on the φ coefficient of association. The analysis splits the data set in two main subclusters; the first one (A) includes few relevés of low altitude, thermophilous conenoses, interpreted as a transition between the submediterranean aspects of Festuco-Brometea class and other Mediterranean herbaceous and shrubby classes; the second subcluster (B) includes most of the data set and can be clearly subdivided in pioneering, mesoxerophilous communities (B1 and B2a groups) and mesophilous communities (B2b group). The relevés of clusters B1 and B2a are referred to Coronillo minimae-Astragaletum monspessulanii association and to three other groups: Plantago argentea-Carex caryophyllea communities, Tragopogon samaritani-Bromus erectus communities, Festuco trachyphyllae-Brometum erecti ass. nova. The mesophilous group (B2b) includes the original Centaureo bracteatae-Brometum erecti and Ononido masquillerii-Brometum erecti relevés, together with a slightly differentiated community; due to the non-relevant differences between these grassland types from floristic, ecological and chorological perspectives, we propose herewith to treat them as three subassociations of Centaureo bracteatae-Brometum erecti (typicum, ononidetosum masquillerii and linetosum cathartici). Post-cultural grasslands in human-disturbed areas were also detected. All these communities can be attributed to Polygalo mediterraneae-Bromenion erecti suballiance (Bromion alliance), even if a clear subdivision between the mesoxerophilous pioneer aspects and the more mesophilous and evolved ones can be noted.